Pursuing Quality Education in Physical and Rehabilitation Medicine in Japan - Asami, Toyoko (Frontiers in Rehabilitation Sciences, 2022)
In Japan, medical education and training are the combined responsibility of two ministries namely Ministry of Education, Culture, Sports, Science and Technology, and the Ministry of Health, Labor and Welfare. The medical education system underwent a major transformation in August 2021 making it a seamless clinical education blending pre-graduation and post-graduation training. Not all universities offer rehabilitation medicine curriculum. Furthermore, where rehabilitation medicine is taught, the curriculum content is not standardized. All medical students sit for a common national medical practitioner qualifying examination. However, only a few questions on Rehabilitation Medicine are included. The personal experience of the author's teachings in rehabilitation medicine at Saga University medical school is described. Emphasis is placed on experiential learning on subjects that are current and state-of-the-art in Japan including robotics. It is aimed at promoting inspired motivation for the students to pursue specialized training in rehabilitation medicine. Japan can take lessons from the European Union's white book on Physical Medicine and Rehabilitation as well as the International Society of Physical and Rehabilitation Medicine core curriculum. In addition, the Rehabilitation Medicine education system can be further improved through a well-coordinated preclinical and clinical medical education. There is also a need to expand the rehabilitation medicine field and address the gaps with other specialties.